Ramification of alcohols towards microalgae fatty acid esters recovery via direct transesterification - Abu Hassan, Muhammad Syafiq; Mohd Yusmadi, Aina Irdina; Nik Him, Nik Raikhan (Universiti Teknologi MARA Shah Alam, 2025)
Alcohols are commonly utilised for methyl or ethyl esters production in the transesterification of biodiesel production; a non-petroleum-based energy sources which is mostly cited as mono-alkyl esters. The substantial needs of high reactant concentration and catalyst have diverted studies towards direct transesterification (DT). Traditional physicochemical disruption towards microalgae cells which aims for free fatty acids collection commonly goes all along with the DT which reducing a lot of cost and chemical dependency. The aimed fatty acid methyl esters (FAMEs) and fatty acid ethyl esters (FAEEs) were transesterified using freshly harvested Chlorella sp. 15g/L HCDs of wet microalgae and alcohol with ratio of 1:3 microalgae oil to alcohol were used in utilising the DT. This method could provide higher reaction rate as well as a shorter reaction time and promoting a higher purity of biodiesel. The objective of this study is to observe the effect of ethanol and methanol as acylation agent in producing biodiesel via direct transesterification of Chlorella sp. The Fourier-Transform Infrared Spectroscopy (FTIR) and Gas Chromatography Mass Spectrometry (GC/MS) were used to determine the purity and the characteristics of the alcohol affecting the DT. The biodiesel from methanol solvent provides higher purity product since it was more soluble and less dense compared to the ethanol, which enhanced the reactivity of DT. The final mass of FAME was lower compared to FAEE; 1.528 gram and 2.691 gram, respectively. This is due to the simple structure of methanol, which enhanced the bond breaking as well as vaporisation at a lower temperature. Final FAME product was characterised as butenoic acid, 3-methyl-, methyl ester with purity of 37.84 %, and FAEE product was a 9-octadecenoic acid (Z)-, methyl ester with purity of 15.75 %. In conclusion, direct transesterification using methanol was more effective than ethanol due to its molar ratio.